Instrumentação e metodologias de mediçãode biopotenciais - Adriano Silva Vale Cardoso (2010)
Biopotential measurement and recording can be seen as a valuable resource in the quest for the understanding of biological systems working principles. It is also a very important tool for medical diagnosis, widely known and accepted in medical literature. Devices used for biopotentialrecording are subject of research for a long time, and has improved its characteristics towards more reliable measurement systems. This fact made possible the assessment of new circuits and methods, which, in some cases, represented important achievements for electronic instrumentation. The purpose of this work is the study of biopotential recording systems, focused on the design and evaluation methods for electronic instrumentation. Consequently, improvements are proposed inthese methods and also, new circuits are presented to solve specific problems of the measurement process. The monitoring of cardiovascular physiological parameters are specially concerned, and are achieved through electrocardiogram (ECG) and blood pressure recording in experimental animals. Contributions regarding ECG recording methods are presented. Several hardware modules were constructed in order to reproduce results from technical literature, to validate the proposed design procedures and to demonstrate the effectiveness of the proposed new circuits. Experimental results obtained from aforementioned hardware modules are presented.